An Analysis of Students’ Errors in Writing Narrative Text - Rauldatul Husni; Martiya Nurni Khairita; Liza Panobiyasari (Innovative: Journal Of Social Science Research, 2023)
This study aims to analyzed errors in the used of simple past in narrative text and writing comprehension in the tenth grade of SMAN 1 Sitiung. The problems of this research are students can not difference about simple past, students did not understand the formula of simple past, students made grammatical errors when they used simple past tenses. The aims of this research are to find out the kinds of errors made by the students on the used of simple past to find out the dominant error on the used of simple past tense in narrative text. The methode of this research is qualitative research. The sample in this study was class X MIPA 3. The research found several problems in the class. Therefore the researcher analyzed the types of errors made by the students. The findings of this study indicate that there are 4 types of errors frequency being omission with 45 (51.14%), followed by misformation with 17 (19.32%) then addition with 15 (17.05%) and the last one misordering with 11 (12.5%). Based on the results of the study, The concluded that most students still feel confused and therefore still make mistakes when writing English texts, especially narrative texts